Transcriptomics Analysis Of Coding Genes And Long Non-Coding Rnas In Ageing In Drosophila Melanogaster - Hosseinzadeh Bajgiran, Mohammad Morteza (2022)
Ageing is characterised by the loss of physiological and cellular functions, the loss of tissue structure, and deterioration of molecular interactions, leading to chronic diseases such as diabetes, cancers, neurodegenerative diseases, and other age-related diseases. Due to the genetic conservation, the genes and pathways underlying ageing were found to have comparable pattern across different species. These genes and pathways have been categorised into nine cellular and molecular hallmarks, namely, genomic instability, telomere attrition, loss of proteostasis, mitochondrial dysfunction, epigenetic alterations, deregulated nutrient sensing, stem cell exhaustion, cellular senescence and altered intercellular communication. The main objectives of this research are to understand how the expression levels of coding genes change during ageing and to identify lncRNAs involved in the process of ageing. To determine the best time points that represent young adult, middle age adult and old adult of D. melanogaster, the survival curve was determined and accordingly three time points, day 1, day 30, and day 60, were chosen.